THE STUDENT IS CONSTITUTIONAL LAW, HAVE PROFESSIONAL DUE PHYSICAL EDUCATION ENTITLED TO OFFER YOU CONTENT AND LEARNING ASSESSMENT IN BASIC EDUCATION. (Fiep Bulletin - online, 2016)
This article aims to demonstrate the legal and pedagogical implications practiced by the administrative action taken by the Recife City Hall, to allow Professor of Fundamental I Education classroom (1st to 5th), at the expense of Professor of Physical Education, enabled the exercise of the profession in Basic Education, which runs counter to constitutional provisions necessary for the exercise of citizenship and qualification for work of the student, and the quality of education, a constitutional guarantee.
Keywords: Education. Citizenship. Warranty.